Analisis Konsepsi Belajar Perspektif Al-Qur’an - Muhammad Aziz Husnarrijal (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2021)
This article discusses the concept of learning according to the view of the Qur'an. The Qur'an emphasizes that learning is a process of seeking knowledge that involves humans and God; transmission of knowledge that makes humans as creatures who are not only kind to other creatures, but also makes humans good servants and obedient to His commands. The method in this research is through a qualitative approach with an analysis of the literature review. Some of the findings in this research include: learning methods according to the Qur'an such as the process of imitation, practical experience and thinking, motivational principles, repetition, attention, active participation, learning sharing, and gradual behavior change.